A collective case study of athletic identity and successful injury rehabilitation - Jama, Kaisa-Mari (2015)
A severe injury is an identity threatening situation for competitive athletes. Previous literature suggests that having a strong athletic identity can be beneficial for the athlete when injured. To the date there has been little research on how athletic identity is managed during that challenging time of injury. The purpose of this study was to explore how athletic identity is managed during the injury and rehabilitation phase before returning to competitive sport. Knowing the determinants of athletic identity management allows practitioners to adjust their interventions toward specific issues when working with injured athletes.